An Integrated Computational Approach for Optimizing Wageningen B-Series Marine Propellers and Assessing Open Water Performance through CFD Simulation - Muhammad Ali Reza; Lilik Khoiriyah; Muhammad Fiky Izzulhaq; Intan Rahmahwati; Vena Rizky Pusparani; Chezta Ahmad Muzakky (National Research and Innovation Agency (BRIN Publishing), 2025)
This study investigates the optimization of Wageningen B-series marine propellers using a CFD-based approach combined with numerical solver techniques to improve hydrodynamic performance under operational constraints. Key design parameters, including blade number, diameter, pitch ratio, and expanded area ratio, were optimized while satisfying thrust, cavitation, and structural limits. Propeller performance was evaluated in terms of thrust coefficient (KT), torque coefficient (KQ), and open water efficiency (η), with and without the application of Propeller Boss Cap Fins (PBCF). The optimized configuration consists of a three-bladed propeller, achieving a maximum efficiency of 0.51347 while meeting all imposed constraints. Results show that the inclusion of PBCF reduces KT, KQ, and η at low to moderate advance coefficients, but yields efficiency improvements at higher advance coefficients, particularly at J = 0.8. The findings demonstrate that CFD-based constrained optimization provides an effective alternative to conventional chart-based propeller design methods and highlights the importance of matching propeller modifications to specific operating conditions.